(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This study investigates the feasibility and environmental impact of utilizing innovative substances as replacements for traditional raw materials in paper production. Five alternative substances, including agricultural residues, hemp fiber, recycled materials, algae, and bamboo, were analyzed based on their availability, sustainability, and papermaking properties. Results indicate promising alternatives to wood pulp, with significant implications for the sustainability of the paper industry